1966
DOI: 10.1037/h0023867
|View full text |Cite
|
Sign up to set email alerts
|

Preference behavior in an immediate versus variably delayed shock situation with and without a warning signal.

Abstract: 3 studies are reported investigating human preference for immediate vs. variably delayed shock with and without a warning signal. The information-preparation theoretical statements of Berlyne and Perkins were used for predicting that immediate shock would be preferred under 100% shock with no warning signal for the delayed condition and that this preference would be prevented or reversed when shock occurred only 25% of the time and a warning signal preceded delayed shock. Study 1 (N = 20) used an unstructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 7 publications
1
32
1
Order By: Relevance
“…Secondly, we find a correlation between dread and social discounting, such that people who more strongly prefer immediate pain show steeper social discounting of pain, and thereby tend to be less altruistic overall. In keeping with previous findings, participants chose to speed up the delivery of pain both for themselves or others, even if this entailed an increased intensity of the pain, consistent with an effect of dread (Badia et al, 1966;Berns et al, 2006;Cook & Barnes, 1964;Hare, 1966a;Loewenstein, 1987;Story et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Secondly, we find a correlation between dread and social discounting, such that people who more strongly prefer immediate pain show steeper social discounting of pain, and thereby tend to be less altruistic overall. In keeping with previous findings, participants chose to speed up the delivery of pain both for themselves or others, even if this entailed an increased intensity of the pain, consistent with an effect of dread (Badia et al, 1966;Berns et al, 2006;Cook & Barnes, 1964;Hare, 1966a;Loewenstein, 1987;Story et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…In this situation, the animals appeared extremely agitated, a condition he described as experimental neurosis (described in Windholz, 1990). Further, when human subjects are given a choice between uncertainty about future shock delivery and predicted immediate shock, they prefer imminent immediate shocks, exhibiting an aversion to uncertainty about the future delivery of shocks (Badia et al, 1966). Thus, cognitive uncertainty can generate a similar stress response as other threatening stimuli (Greco and Roger, 2003); further, it has been proposed that a low threshold to uncertainty is a reliable cognitive marker of depression susceptibility (Liao and Wei, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies provide empirical evidence for the linkage between uncertainty and stress. In the laboratory, for example, research has shown that anxiety increases when individuals receive unpredictable shocks as opposed to immediate, expected ones (e.g., Badia, McBane, Suter, & Lewis, 1966;Lanzetta & Driscoll, 1966;Pervin, 1963). Similarly, in the field, research has demonstrated that job-related uncertainty is associated with stress (Bordia, Hobman, Jones, Gallois, & Callan, 2004;Mantler, Matejicek, Matheson, & Anisman, 2005;O'Driscoll & Beehr, 1994).…”
Section: Justice Variability and Stressmentioning
confidence: 99%